DYSTONIA IN CHILDREN (A LECTURE) - M. Yu. Bobylova; V. S. Kakaulina; E. S. Ilyina; I. V. Nekrasova; N. L. Pechatnikova; S. V. Mikhailova; M. B. Mironov; K. Yu. Mukhin (Русский журнал детской неврологии)
Distonia is a movement disorder associated with imbalance of excitatory neurotransmitters, and it is characterized by continuous or episodic muscle contraction that forms repetitive stereotyped movements and/or postures. Dystonic hyperkinesia of younger children can be included into the structure of many syndromes that have different etiological factors, prognosis, and treatment. Different clinical variant of dystonia are represented: idiopathic benign dystonia with the onset in the first year of life; dystonia against the background of residual damage to the nervous system; hereditary idiopathic and symptomatic dystonia with various syndromes and metabolic diseases; similar conditions. Diagnostics of dystonia of children requires application of a wide range of examinations, including neuroimaging, continuous video electroencephalographic monitoring, genetic research. Differential diagnosis of dystonia of children is performed regarding various paroxysmal states of childhood of the epileptic and non-epileptic nature.